The Role of the Government Internal Oversight Apparatus in Preventing Corrupt Practices through the ‘Inspektorat Goes to School’ Programme in Sidoarjo Regency - Ike Prasetyadewi Subehti; Aris Sunarya; Amirul Mustofah (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2026)
Corruption remains a structural problem that hampers good governance in Indonesia; efforts to combat it therefore cannot rest on enforcement alone but must also encompass prevention at an early stage. This study aims to analyse the role of the Government Internal Oversight Apparatus (Aparatur Pengawas Internal Pemerintah, APIP) — embodied at the regional level by the Regional Inspectorate — in preventing corrupt practices through the educational programme ‘Inspektorat Goes to School’ in Sidoarjo Regency. The programme positions schools as spaces for value formation and targets junior secondary school pupils as the generation that will shape the bureaucracy of the future. The study adopts a descriptive qualitative approach, with data gathered through a documentary study of official reporting, policy documents, and regional government publications, which were then analysed thematically with reference to theories of corruption prevention and character education. The findings show that APIP performs consulting and assurance functions that shift from a repressive towards a preventive orientation through the internalisation of nine integrity values, namely honesty, caring, independence, discipline, responsibility, hard work, simplicity, courage, and justice. The strategy pursued rests on three pillars — prevention, education, and corrective action — and is reinforced through the appointment of Anti-Corruption Ambassadors in each school. The programme targets 27 schools in 2026 and is positioned as a sustained movement rather than a ceremonial activity. The study concludes that extending the role of APIP into the domain of character education constitutes a governance innovation that strengthens the internal oversight function in breaking the chain of corruption at the upstream source of the problem, whilst also demanding continuity, cross-stakeholder collaboration, and measurable instruments for evaluating impact.